Educación e Inteligencia Artificial: Un Análisis desde la Perspectiva de los Docentes en Formación - Goenechea, Cristina; Valero-Franco, Concepción (REICE. Revista Iberoamericana sobre Calidad, Eficacia y Cambio en Educación, 2024)
AI affects education in at least three distinct areas: decision-making regarding educational systems; teaching-learning processes and the need to update the understanding of civic education. In this article, a quantitative approach was taken to examine the extent to which future primary education teachers are aware of concepts related to AI; their understanding of how it may transform education; and its link to the 8 key competencies of our educational system. We analyzed the extent to which responses differ depending on the gender and prior studies of the students. The results reveal significant differences, with men and students from science baccalaureate programs perceiving themselves as being more knowledgeable about AI. The students tended to link AI to digital and mathematical competencies as well as science, technology, and engineering competencies. Very few links were made to the civic competence. The students were aware that AI will influence almost all aspects of education (methodology, way of learning, teacher’s role, etc.) and they requested additional training in this area.